Informe Mosaico 5 A Malargüe, Mendoza. Plan Mendoza - Dalponte, Daniel Oscar (1976)
Fil: Dalponte, Daniel Oscar. Ministerio de Economía. Subsecretaría de Minería. Servicio Nacional Geológico Minero; Argentina